The effect of intangible factors on innovation capabilities in higher education institutions - Nur Balqishanis, Zainal Abidin (2020)
Innovation plays an important role in the development of any organization including higher education institutions (HEIs) that forced many researchers to embark on this issue. HEIs should be the role model in the practice of innovation so as to encourage and empower innovation for the survival of research institution. Therefore, the aim of this study is to examine the structural relationships in the hypothesized model that comprised of critical factors, namely, objectives and strategy, change management, resource management, best practices and innovation. A total of nine hypotheses have been put forward to test the relationships amongst these five critical factors of innovation capabilities model. Theoretical framework that integrates all five factors is also introduced. Partial least squares structural equation modeling technique was used to empirically assess the model. The primary data was collected through innovation exhibitions using questionnaire that was adopted and adapted from previous study, in which convenience-sampling technique was employed on local public and private universities that generated 213 valid responses. The findings revealed that all the hypothesized relationships are significant at t-value > 2.58 of two-tailed test by using 5000 bootstrapped samples, except for the relationship between resource management towards innovation that resulted in a non-significant relationship. The result of these significant relationships, verified the proxies in the model. The implications of this research would provide the guidelines or ideas towards management and administration in the university in order to achive better performance by practicing the core values that categorized as intangible indicators. Moreover, throughout this developed model could be the basis for HEIs, especially in Malaysia, to accelerate their innovative capability by garnering all the efforts and endeavor for achieving excellence and be recognized worldwide.